Conscious awareness, sensory integration, and evidence accumulation in bodily self-perception - Renzo C. Lanfranco; Sucharit Katyal; August Hägerdal; Xiaole Luan; Victoria Nos; H. Henrik Ehrsson (Proceedings of the National Academy of Sciences, 2025)
Conscious awareness refers to the subjective experience of perceiving, thinking, and feeling and the ability to report these experiences. These perceptions and thoughts are experienced as bound to an individual self. A fundamental aspect of this self-consciousness is the sense of bodily self—the experience of one’s physical presence distinct from the external world, serving as the spatial reference point for conscious perceptions. A key component of the bodily self is body ownership, the experience of the body as one’s own. Research shows this sense involves integrating signals from different sensory modalities, including vision, touch, and proprioception, into a coherent multisensory percept. However, the relationship between body ownership and conscious awareness remains unclear. To investigate this, we developed a psychophysical paradigm to objectively quantify multisensory integration, conscious awareness, and their relationships within a bodily illusion manipulating body ownership perception. Using signal-detection analysis, metacognitive computational modeling, and drift–diffusion modeling, we found conscious awareness reports closely matched objective discrimination of body ownership. This relationship remained consistent across different levels of multisensory integration and evidence accumulation. A visuotactile control experiment revealed that this strong conscious access is specific to body ownership, not general to multisensory integration. These findings suggest that conscious awareness has continuous and prioritized access to body ownership, implying that the self-related form of multisensory integration supporting body ownership is largely implemented at the level of conscious processing. This provides theoretical insight into how conscious awareness and the bodily self are intertwined, with wide-reaching implications for consciousness and body representation research.